Penerapan Model Strategi Keunggulan Bersaing Berorentasi Lingkungan Pada Perguruan Tinggi Swasta (PTS) Di Kota Semarang - NURCHAYATI NURCHAYATI; Imam Gozali (Serat Acitya, 2015)
The Research oriented application environment competitive advantage strategy on Perguruan Tinggi Swasta (PTS) in Semarang with qualitative descriptive analysis tools produce information models ( 1 ) information technology ( IT ) services in support of very large. ( 2 ) The business strategy is carried out by PTS in Semarang with the strategy of market penetration , market development, product development, concentric diversification and horizontal stretegi able to improve organizational performance ( 3 ) The orientation of the customer ( student ) related to the needs of the stakeholders , ( 4 ) Orientation competitors and ( 5 ) environmental orientation to achieve competitive advantage. Informants in this study is the dean or a representative. The results of the phase II study recommends that the environmental dimension there are some private universities are not yet possess the green room and lobby space is adequate, there are private universities that do not have lifts for the disabled , all PTS has been to build relationships with the Company and the Bank, a small portion yet formed a partnership with IDX, most of PTS is not the concept of nationalism, and religion -based Key Word : information technology ( IT ), business strategy,  Market orientation, and environmental orientation